Forced migration: Typology and local agency in Southeast Myanmar - Ashley South (2018)
© 2015, ISEAS–Yusof Ishak Institute. Ethnic armed conflict has plagued southeast Myanmar for over sixty-five years, and has been the cause of significant and repeated episodes of forced migration. The dynamics of forced migration have undergone profound changes in the region since 2012, following the signing of bilateral ceasefire agreements between the government and several Ethnic Armed Groups (EAGs). Within this context, this article describes and analyses the decision-making processes and approaches to return, resettlement and rehabilitation of forced migrants — Internally Displaced People (IDPs) and refugees. In relation to academic and policy literatures on local agency and humanitarian protection, we argue that forced migrants in and from Myanmar demonstrate great resilience and significant capacities for self-protection and that external support should be geared towards supporting local coping strategies and attempts to achieve dignified and “durable solutions” to their plight. This approach requires an in-depth exploration of local contexts, and forced migrants’ decision-making processes. We present a typology of conflict-induced forced migrants in and from southeast Myanmar, followed by an analysis of five main factors that influence their decisions, and help to explain some of the key differences between different types.